Bioengineering a humanized 3D tri-culture osteosarcoma model to assess tumor invasiveness and therapy response - Monteiro, Cátia F. (2021)
To date, anticancer therapies with evidenced efficacy in preclinical models fail during clinical trials. The shortage of robust drug screening platforms that accurately predict patient's response underlie these misleading results. To provide a reliable platform for tumor drug discovery, we herein propose a relevant humanized 3D osteosarcoma (OS) model exploring the potential of methacryloyl platelet lysates (PLMA)-based hydrogels to sustain spheroid growth and invasion. The architecture and synergistic cell-microenvironment interaction of an invading tumor was recapitulated encapsulating spheroids in PLMA hydrogels, alone or co-cultured with osteoblasts and mesenchymal stem cells. The stem cells alignment toward OS spheroid suggested that tumor cells chemotactically attracted the surrounding stromal cells, which supported tumor growth and invasion into the hydrogels. The exposure of established models to doxorubicin revealed an improved drug resistance of PLMA-based models, comparing with scaffold-free spheroids. The proposed OS models highlighted the feasibility of PLMA hydrogels to support tumor invasion and recapitulate tumor-stromal cell crosstalk, demonstrating the potential of this 3D platform for complex tumor modelling. STATEMENT OF SIGNIFICANCE: Cell invasion mechanisms involved in tumor progression have been recapitulated in the field of 3D in vitro modeling, leveraging the great advance in biomimetic materials. In line with the growing interest in human-derived biomaterials, the aim of this study is to explore for the first time the potential of methacryloyl platelet lysates (PLMA)-based hydrogels to develop a humanized 3D osteosarcoma model to assess tumor invasiveness and drug sensitivity. By co-culturing tumor spheroids with human osteoblasts and human mesenchymal stem cells, this study demonstrated the importance of the synergistic tumor cell-microenvironment interaction in tumor growth, invasion and drug resistance. The established 3D osteosarcoma model highlighted the feasibility of PLMA hydrogels as a relevant 3D platform for complex tumor modelling.